Cell cannibalism: a diagnostic and prognostic marker of breast cancer - Mohsin, Mir; Zargar, Haroon Rashid; Khan, Mohammad Amanullah; Sherwani, Rana (International Surgery Journal, 2020)
Background: Cell cannibalism (cytophagocytosis) is defined as a tumor cell within a tumor cell, such that smaller tumor cells are found in the cytoplasm of larger tumor cells with crescent shaped nuclei. Aims and Objectives were to study the cytomorphological characters of cell cannibalism in primary and metastatic breast cancer, to correlate the histologic type and grade of tumors with positive rate of cannibalism and to study the role of Cannibalism as an independent prognostic factor in breast cancer. Methods: The study was conducted during the period of July 2003 to June 2005 in the Department of Surgery and Pathology, JNMCH, Aligarh. A total of 42 cases were included in the study. A minimum of 3 FNAC smears per case were assessed for cytophagocytosis. Presence of metastasis was also noted to establish the cytological grade and aggressiveness of the tumor. Results: Out of 42 cases, significant cannibalistic activity was noted in 30 (71.42%) cases. All grade III (33.4%) breast tumors were found positive for cytophagocytosis (4.28/smear), while the rate was much lower (2.33/smear) in grade II and (1.63/smear) in grade I tumors. LN metastasis was confirmed by histopathological examination in all high grade tumors showing significant cannibalistic activity. Conclusions: Cannibalism in breast carcinoma is an indicator of both the anaplastic grade and invasiveness. The rate of cytophagocytosis may have a prognostic significance.